European energy journal (Claeys & Casteels Law Publishers, 2011)
"The EEJ offers the practitioner and the academic pro-active information on energy law and policy throughout Europe. It reports and comments relevant developments in the areas of internal market competition law, energy efficiency, renewable energies, climate change, infrastructure, security of supply, and foreign energy policy. Each issue includes regular reports on legislative initiatives, case law and country developments"--Publisher's website.